Pacific economic monitor - Asian Development Bank. (Metro Manila, Philippines Asian Development Bank, 2018)
The December 2018 issue of the Pacific Economic Monitor provides an update on developments in 14 Pacific economies and explores topical policy issues in the region. This publication provides an update on developments in Pacific economies, explores topical policy issues in the region over the years, and presents global forecasts for 2019. It includes an outline of the economic setting, as well as country economic issues and specific policy briefs for 14 Pacific economies. This includes analysis of critical development challenges including connectivity, climate change and disaster resilience, tourism, fisheries, and public sector management. The December 2018 issue also focuses on debt sustainability amid clear financing needs to help address remaining infrastructure and services gaps in the Pacific.
Keywords: Pacific Area -- Economic conditions; Electronic books